The role of entrepreneurial orientation in adopting creative strategies: An analytical study in the General Company for Petroleum Products in Nineveh Governorate (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2025)
The study aimed to test the role of entrepreneurial orientation in terms of its dimensions (proactiveness, initiative, risk tolerance, independence) in adopting Creative strategies in terms of its dimensions (first mover strategy, alliance strategy, and technology leadership strategy), within the framework of testing the relationships of correlation and impact between them in the field investigated. The study adopted the descriptive analytical approach, and adopted the questionnaire as the main tool in collecting data from a sample   of (56) respondents. It used statistical analysis tools according to statistical programming (SPSS.26), and reached several results that confirmed the existence of correlations and influence between entrepreneurial orientation and Creative strategies in the researched field.